Perfomance Pejabat Fungsional Kemanker yang Proses Pengangkatan Melalui Inpasing - Wardoyo, Bambang; Adil, Athira Setira; Abrian, Muhammad Eko (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study investigates the effects of motivation, compensation, and job satisfaction on the performance of functional civil servants transitioning through the inpassing mechanism. Using a quantitative approach and SmartPLS for data analysis, the research examines both direct and indirect relationships among these key variables. Data were collected from a number of respondents who experienced the inpassing process, offering valuable insights into employee perceptions and outcomes.The findings reveal that motivation has a significant and direct influence on both job satisfaction and performance, making it the most dominant factor in the model. Compensation also exerts a positive and significant effect on job satisfaction, although its impact on performance is more moderate. Interestingly, while job satisfaction shows a positive relationship with performance, this connection is not statistically significant. Model evaluation demonstrates that motivation and compensation together explain 59% of the variance in job satisfaction and 48% in performance.These results underscore the importance of intrinsic motivation and a fair compensation system in improving employee performance, particularly during organizational transitions. The study contributes both theoretically and practically by providing a better understanding of what drives performance in the public sector. It highlights the urgent need for strategic HR policies that strengthen internal motivation and ensure fair treatment, especially for employees shifting roles through inpassing.